BOSHLANG‘ICH SINF O‘QUVCHILARI UCHUN MANTIQIY MASALALAR TUZISH VA ULARNI YECHISH METODIKASI - UMAROVA ZULFIZAR OTABEK QIZI (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article examines the importance of logical problems for the development of logical thinking in primary school students, the methodology for their formulation and solution. By using logical problems in primary school mathematics lessons, students can develop skills such as independent thinking, analysis, and identification of logical relationships. The article discusses the types of logical problems and analyzes the aspects that should be paid attention to when formulating them. It also provides effective methods for solving logical problems, innovative pedagogical approaches, and recommendations based on experimental results.